Kendala Penerapan BIM dalam Praktik Perancangan: Tinjauan Sistematis di Negara Berkembang - Hagan, Daniel Ebo; Aryanti, Tutin; Ilhamdaniah, Ilhamdaniah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
Despite the progress made with BIM integration into the construction industries of many developed countries, its adoption remains limited in most developing countries. This study systematically reviews 56 articles using the TOE framework to identify and analyse critical barriers that impede BIM implementation within architectural design contexts. Following the PRISMA guidelines, the review categorizes these barriers into three primary dimensions: technological, organizational and environmental. The results revealed that critical technological barriers, such as the high cost of hardware and software, compatibility issues with design tools, and technical complexities in using the technology, hinder architectural innovation and visualization capabilities. Organizational barriers, including insufficient BIM-trained professionals, lack of awareness of BIM capabilities, resistance within design teams and lack of management support, significantly delay BIM integration in design studio workflows. Environmental barriers such as insufficient regulatory frameworks, lack of client demand for BIM-based project design, and weak collaboration across multidisciplinary consultants slow the adoption of digital design practices. The study underscores the interrelated characteristics of these critical barriers, which form a perpetuating cycle that limits the evolution of design practices in developing countries. Addressing these interrelated barriers is crucial for improving design creativity and integrating BIM into studio practices. Future research should examine regional variances and pedagogical strategies for overcoming the BIM adoption challenges in architectural contexts.